Establishing the Fundamentals of the TRIZ application to the development or improvement of SMEs Business Models (2021)
In Colombia, Small and medium enterprises, SMEs, play a fundamental role in the economy. SMEs contribute about 80% of the labor force that generates 35% of GDP. However, by the second year of their operation, about 70% fail and disappear which affects the economic performance. There are many reasons why SMEs fail early, among which we can mention the lack of strategic planning and analysis of the environment, the ambition to grow rapidly coupled with the lack of long-term planning. SMEs fail, among other reasons, because of lack of innovation and their inefficient business models. Innovation might be a good tool to avoid early failures. The goal of this master?s degree document is to lay the foundations for the research that should answer the question: does the TRIZ innovation methodology have the potential to develop SMEs? new business models or improve existing ones? Therefore, the hypothesis raised here states that, the TRIZ innovation methodology has tools that enables the development or improvement of SMEs? business models. This hypothesis will be validated during the investigation that we will be carried out during the course of the Doctorate in Technological Innovation Management that will take place during the following semesters. The final goal of the doctorate program is to develop a service model, based on TRIZ and the Business Model Canvas (BMC) to allow SMEs either to develop or improve their business models so that they can be differentiated, innovative and sustainable. The methodology applied in this project consists of executing four experiments in order to validate the desirability, feasibility and viability of the proposed service. The results obtained allow us to conclude that the application of TRIZ to each of the nine modules of the BMC is feasible, viable and desirable, which sets the foundations for the long-term doctorate project.